Biocontrol Potential of a Novel Endophytic Bacterium From Mulberry (Morus) Tree - Xie, Sen; Vallet, Marine; Sun, Chao; Kunert, Maritta; David, Anja; Zhang, Xiancui; Chen, Bosheng; Lu, Xingmeng; Boland, Wilhelm; Shao, Yongqi (Frontiers in Bioengineering and Biotechnology, 2020)
Mulberry (Morus) is an economically important woody tree that is suitable for use in sericulture as forage and in medicine. However, this broad-leaved tree is facing multiple threats ranging from phytopathogens to insect pests. Here, a Gram-positive, endospore-forming bacterium (ZJU1) was frequently isolated from healthy mulberry plants by screening for foliar endophytes showing antagonism against pathogens and pests. Whole-genome sequencing and annotation resulted in a genome size of 4.06 Mb and classified the bacterium as a novel strain of Bacillus amyloliquefaciens that has rarely been identified from tree leaves. An integrative approach combining traditional natural product chemistry, activity bioassays, and high-resolution mass spectrometry confirmed that strain ZJU1 uses a blend of antimicrobials including peptides and volatile organic compounds to oppose Botrytis cinerea, a major phytopathogenic fungus causing mulberry grey mold disease. We showed that the inoculation of endophyte-free plants with ZJU1 signiﬁcantly decreased both leaf necrosis and mortality under field conditions. In addition to the direct interactions of endophytes with foliar pathogens, in planta studies suggested that the inoculation of endophytes also induced plant systemic defense, including high expression levels of mulberry disease resistance genes. Moreover, when applied to the generalist herbivore Spodoptera litura, ZJU1 was sufficient to reduce the pest survival rate below 50 percent. A previously undiscovered crystal toxin (Cry10Aa) could contribute to this insecticidal effect against notorious lepidopteran pests. These unique traits clearly demonstrate that B. amyloliquefaciens ZJU1 is promising for the development of successful strategies for biocontrol applications. The search for new plant-beneficial microbes and engineering microbiomes is therefore of great significance for sustainably improving plant performance.